Penerapan Kaizen Improvement Pada PT DSV Solutions Indonesia - Rechal Wulandari (Jurnal Kendali Teknik dan Sains, 2023)
The purpose of this study is to determine the flow of work processes in the warehouse from the inbound, inventory and outbound processes, follow mentoring held every week by doing post test and pre test mentoring, and identify opportunities for improvement in the warehouse in an effort to reduce waste. The research method used by the author in this study is continuous improvement, or kaizen. The results showed that almost about 50% of the writers' activities at PT. DSV Solution Indonesia deals with labeling products with K3L (Safety, Occupational Health &; Environment) labels. This product labeling activity requires a level of accuracy and concentration so that the goods labeled are in accordance with the established category. The products labeled are footware or footwear products such as shoes or sandals. Both shoes and sandals each have an identical number of different K3L labels, not only that each category of product type is then distinguished again according to the origin or origin of the product made. The origin of products that go through the K3L label stage usually comes from Indonesia, Vietnam, and China. So for the number of identical numbers, the K3L label amounts to 6 according to the category of origin and also the type of product.